The optimal time interval between neoadjuvant chemoradiotherapy and surgery for patients with an unfavorable pathological response in locally advanced rectal cancer: a retrospective cohort study - Wang, Litao; Fan, Jianyong; Guo, Yaqi; Shang, Shipeng; Gao, Han; Xu, Jianfei; Gao, Peng; Liu, Enrui (Frontiers in Oncology, 2025)
BackgroundThe focus of this study was to determine the optimal time interval between neoadjuvant chemoradiotherapy (nCRT) and surgery in patients with locally advanced rectal cancer (LARC) who had an unfavorable pathological response, as well as to investigate the correlation between long-term outcomes and the duration of this interval.MethodsThe present study retrospectively analyzed patients with locally advanced rectal cancer who underwent nCRT followed by total mesorectal excision between (TME) January 2018 and September 2021. Patients included in this study had an unfavorable pathological response, confirmed as tumor regression grade (TRG) 2-3. X-tile analysis was subsequently conducted to determine the optimal cut-off value for the time interval between nCRT and surgery. Furthermore, Cox proportional hazards regression analyses were performed to identify independent prognostic factors, and the Kaplan-Meier method was used to estimate long-term survival.ResultsThe study cohort comprised of 114 patients (51.35%) in the longer interval group (>8 weeks), while the remaining 108 patients (48.65%) belonged to the shorter interval group (≤8 weeks). Univariable and multivariate Cox proportional hazards regression analyses revealed that a longer interval time was identified as an independent risk factor for overall survival (HR: 2.14, 95% CI: 1.01-4.55, P=0.048) and disease-free survival (HR: 2.03, 95% CI: 1.09-3.77, P=0.025) among these patients. Moreover, patients in the longer interval group exhibited significantly worse OS and DFS compared to those in the shorter interval group (3-year OS: 87.2% vs 68.2%, P=0.001; 3-year DFS: 80.4% vs 62.7%, P=0.003). Furthermore, similar results were observed in subgroup analyses based on different TRG scores.ConclusionsThe surveillance and monitoring should be promptly conducted following nCRT in order to promptly identify patients with an unfavorable pathological response, who would benefit from timely radical surgery within 8 weeks.